Geraldine Ferraro (interview with former vice-presidential candidate in Greece) - Irene Kamberidou (A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 32, Dec. 1, 1985: 8., 1985)
Kamberidou, Irene (1985). Geraldine Ferraro (interview with former vice-presidential candidate in Greece). SPOTLIGHT, A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no.  32, Dec. 1, 1985: 8.